2022
DOI: 10.1021/acs.langmuir.2c00791
|View full text |Cite
|
Sign up to set email alerts
|

Development of Organic/Inorganic Hybrid Materials for Fully Degradable Reactive Oxygen Species-Releasing Stents for Antirestenosis

Abstract: Despite innovative advances in stent technology, restenosis remains a crucial issue for the clinical implantation of stents. Reactive oxygen species (ROS) are known to potentially accelerate re-endothelialization and lower the risk of restenosis by selectively controlling endothelial cells and smooth muscle cells. Recently, several studies have been conducted to develop biodegradable polymeric stents. As biodegradable polymers are not electrically conductive, double metallic layers are required to constitute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The fact that Mg and Zn promote the formation of free radicals has been confirmed by Jeong et al 48 The study showcased prolonged reactive oxygen species (ROS) generation from a biodegradable hybrid comprised of a poly- l -lactic acid substrate with a Mg/Zn bilayer coating, suitable for stents. The authors revealed that degradation products continued to produce both superoxide and hydrogen peroxide seamlessly, even after the complete dissolution of the metallic films.…”
Section: Discussionmentioning
confidence: 81%
“…The fact that Mg and Zn promote the formation of free radicals has been confirmed by Jeong et al 48 The study showcased prolonged reactive oxygen species (ROS) generation from a biodegradable hybrid comprised of a poly- l -lactic acid substrate with a Mg/Zn bilayer coating, suitable for stents. The authors revealed that degradation products continued to produce both superoxide and hydrogen peroxide seamlessly, even after the complete dissolution of the metallic films.…”
Section: Discussionmentioning
confidence: 81%